Sensitivity and reliability of zinc transporter and metallothionein gene expression in peripheral blood mononuclear cells as indicators of zinc status: responses to ex vivo zinc exposure and habitual zinc intake in humans - Hennigar, Stephen R.; Kelley, Alyssa M.; Anderson, Bradley J.; Armstrong, Nicholes J.; McClung, Holly L.; Berryman, Claire E.; Karl, J. Philip; McClung, James P. (British journal of nutrition, 2021)
Zn is an essential nutrient for humans; however, a sensitive biomarker to assess Zn status has not been identified. The objective of this study was to determine the reliability and sensitivity of Zn transporter and metallothionein (MT) genes in peripheral blood mononuclear cells (PBMCs) to Zn exposure ex vivo and to habitual Zn intake in human subjects. In study 1, human PBMCs were cultured for 24 h with 0–50 µm ZnSO4 with or without 5 µm N,N,N′,N′-tetrakis(2-pyridylmethyl)ethylenediamine (TPEN), and mRNA expression of SLC30A1-10, SLC39A1-14, MT1 subtypes (A, B, E, F, G, H, L, M and X), MT2A, MT3 and MT4 mRNA was determined. In study 2, fifty-four healthy male and female volunteers (31·9 (sd 13·8) years, BMI 25·7 (sd 2·9) kg/m2) completed a FFQ, blood was collected, PBMCs were isolated and mRNA expression of selected Zn transporters and MT isoforms was determined. Study 1: MT1E, MT1F, MT1G, MT1H, MT1L, MT1M, MT1X, MT2A and SLC30A1 increased with increasing concentrations of Zn and declined with the addition of TPEN. Study 2: Average daily Zn intake was 16·0 (sd 5·3) mg/d (range: 9–31 mg/d), and plasma Zn concentrations were 15·5 (SD 2·8) μmol/l (range 11–23 μmol/l). PBMC MT2A was positively correlated with dietary Zn intake (r 0·306, P = 0·03) and total Zn intake (r 0·382, P < 0·01), whereas plasma Zn was not (P > 0·05 for both). Findings suggest that MT2A mRNA in PBMCs reflects dietary Zn intake in healthy adults and may be a component in determining Zn status.